LEGAL CULTURE AS AN IMPORTANT ELEMENT LEGAL SYSTEM - Victoria V. Solovieva (Russian Studies in Law and Politics)
The article is devoted to the analysis of the history and current state of the study of legal culture by theoretical and legal science, the definition of the main trends in modern theoretical knowledge of this subject, the rationale for the need for an integrated approach to understanding legal culture and the identification of the most promising areas for future research. It has been revealed that the common content of all definitions of legal culture are such characteristics as observance of the rules of conduct, the presence of moral convictions, possession of legal knowledge and the ability to apply it, responsibility of a person for his own behavior, awareness of legal values, meanings and attitudes. It is noted that common in the content of all definitions of the category «legal culture» are such characteristics as possession of legal knowledge and the ability to apply it, awareness of legal values, meanings and attitudes, the presence of moral convictions and responsibility of the individual for their own behavior, compliance with the rules of conduct. The analysis of elements of legal culture is carried out. Emphasis is placed on the issue of respect for law (law) as recognition of its social value. The maturity of legal culture is an important factor in establishing the principle of the rule of law in all spheres of public life, the implementation of the legal status of the individual, his rights and freedoms.